The Digital Transformation of Generation Z’s Da’wah Through Information Technology and Artificial Intelligence on TikTok - Dede Ahmad Fauzan; Ilham Maulana; Muhammad Khoirul; Abin Maulana Aksa (Universitas Nurul Jadid, 2026)
This study aims to evaluate the effect of exposure to viral artificial intelligence (AI)-based da’wah content on TikTok on Generation Z’s interest in digital da’wah. This quantitative study involved 30 active TikTok users aged 18–25 through an online questionnaire survey supplemented with qualitative data from open-ended questions. Data were analyzed using simple linear regression with the Microsoft Excel Data Analysis ToolPak. The results of the analysis showed a positive but weak correlation between exposure to AI-based da’wah content and interest in digital da’wah (R = 0.233; R² = 0.054; p = 0.215). This effect was not statistically significant and explained only 5.4% of the variation in interest in digital da’wah. Thematic analysis revealed that while AI-generated da’wah content has the potential to enhance accessibility and the appeal of the message, respondents expressed concerns about the credibility of the source, the loss of personal nuance, and the risk of misinformation. These findings suggest that the virality of AI-generated da’wah content has not yet become a primary driver of Gen Z’s interest in digital da’wah. Other factors, such as personal motivation, social support, and digital literacy, are believed to play a greater role and should therefore be investigated further